(untitled) (The Review of Diabetic Studies, 2025)
Background: Laparoscopic appendectomy is the preferred treatment for acute appendicitis, but conversion to open laparotomy is sometimes necessary. Identifying risk factors for conversion is crucial for surgical planning, patient counseling, and optimizing outcomes. This study aimed to determine the patient, disease, and intraoperative factors associated with conversion from laparoscopic to open appendectomy. Methods: A retrospective observational study was conducted on 250 patients who underwent laparoscopic appendectomy for acute appendicitis at a single institution between January 2020 and January 2025. Data on demographic characteristics, comorbidities, disease severity, and intraoperative findings were collected from medical records. Statistical analyses, including univariate and multivariate logistic regression, were used to identify independent risk factors for conversion. Results: The conversion rate to laparotomy was 12% (30/250). Significant patient-related risk factors included advanced age (mean 41.2 vs. 31.5 years, p<0.05), male gender (83.3% vs. 56.8%, p<0.05), obesity (BMI >30; 60% vs. 28.2%, p<0.01), and a history of prior abdominal surgery (40% vs. 15%, p<0.01). Disease severity was a strong predictor, with significantly higher conversion rates for gangrenous (40% vs. 21.8%) and perforated appendicitis (40% vs. 17.2%), and particularly for abscess formation (50% vs. 9.1%, p<0.001). Key intraoperative factors leading to conversion were dense adhesions (50% vs. 11.4%, p<0.001), unclear anatomy (43.3% vs. 6.8%, p<0.001), and excessive bleeding (33.3% vs. 4.5%, p<0.001). Conversion was associated with worse outcomes, including higher complication rates (26.7% vs. 6.8%, p<0.01) and longer hospital stays (6.5 vs. 3.2 days, p<0.001). Conclusion: Conversion to laparotomy is influenced by a combination of patient-related factors (age, gender, obesity, surgical history), disease severity (gangrenous/perforated appendicitis, abscess), and intraoperative challenges (adhesions, unclear anatomy, bleeding). Recognizing these risk factors preoperatively can enhance surgical preparedness and patient counseling. Conversion should be viewed as a prudent decision to ensure patient safety rather than a procedural failure.